1979
DOI: 10.1093/ajcp/72.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Counts in Capillary Blood

Abstract: Samples of venous and capillary blood were collected simultaneously from healthy adults to assess the accuracy of platelet counts in capillary blood as determined by an automated particle counter. The difference between the mean venous blood platelet count (248,300) and the mean capillary blood count (215,500) was highly significant (P less than .001). For 24% (7/29) of the subjects, the capillary blood platelet count underestimated the venous blood count by greater than or equal to 25%, with three subjects er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
1
13
2
Order By: Relevance
“…In cases of acute malaria, patients are usually febrile and vasodilated, whereas following recovery there may be peripheral vasoconstriction, leading to greater tissue fluid admixture in capillary samples. Previous studies in patients and volunteers without malaria have revealed that the haematocrit and leucocyte levels tend to be higher in capillary blood samples than in venous blood samples, while platelet numbers tend to be similar or lower [57,27, 34]. Haematocrit measurements have also been observed to be more variable on repeated capillary sampling than on repeated venous sampling.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of acute malaria, patients are usually febrile and vasodilated, whereas following recovery there may be peripheral vasoconstriction, leading to greater tissue fluid admixture in capillary samples. Previous studies in patients and volunteers without malaria have revealed that the haematocrit and leucocyte levels tend to be higher in capillary blood samples than in venous blood samples, while platelet numbers tend to be similar or lower [57,27, 34]. Haematocrit measurements have also been observed to be more variable on repeated capillary sampling than on repeated venous sampling.…”
Section: Discussionmentioning
confidence: 99%
“…These differences, the opposite to those found by us, are hard to explain but do not appear to be related to the use of a tourniquet, which can falsely raise venous values when used excessively (Hall & Malia 1984), as both Moe and we ourselves used one routinely in obtaining venous samples. Although our finding of higher skin puncture values is not new-for example Feusner et al (1979) presented data indicating a significantly higher skin puncture haematocrit-we are not aware of other studies which have stressed this fact or which have attempted to measure the size of the difference in skin puncture red cell values. The coefficients of variation for Hb, RBC and haematocrit previously determined for our methods using both venous and skin puncture blood (Hinchliffe et al 1985) are in each case less than the difference between the mean values, indicating a real difference between the two groups and a lack of effect on precision of the small volume of skin puncture samples.…”
Section: Discussionmentioning
confidence: 72%
“…Comparisons between skin puncture and venous blood count values in children and adults have previously been made with conflicting results regarding both Hb and RBC values (Andresen & Mugrage 1938;Moe 1970) and platelet counts (Feusner et al 1979;Mayer et al 1980;Lippi et al 1985). A study of these divergent reports prompted us to compare venous blood count data with those obtained from skin puncture samples in children being treated at this hospital.…”
mentioning
confidence: 99%
“…Another similar study [4] on healthy volunteers had shown lower platelet counts, elevated white counts and haemoglobin values in capillary blood compared to venous samples. Other studies [5,6] on platelet counts in healthy volunteers and patients with known low platelet counts noted the difference between the capillary and venous platelet counts to be higher in the healthy volunteers, while there was poor correlation between the venous and capillary samples in patients with low platelet counts. Although it is not clear why the contradiction in the results especially with regards to platelet counts, one possible explanation could be the delay in analysis of the capillary samples sent to the laboratory in the former study [4].…”
Section: Discussionmentioning
confidence: 92%
“…However, there have been conflicting results from several studies that show significant differences between the capillary and venous FBC parameters that are measured [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%